2009
DOI: 10.1590/s0073-47212009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite genotyping from faeces of Lontra longicaudis from southern Brazil

Abstract: ABSTRACT.A genetic study of the neotropical river otter Lontra longicaudis (Olfers, 1818), which has an unknown conservation status, was carried out at the Taim Ecological Station and the margins of the Vargas stream, Rio Grande do Sul, southern Brazil. Faecal samples were collected, and DNA was extracted using a silica-guanidine method. Five microsatellite loci were amplified using PCR with heterologous primers previously described for Lutra lutra (Linnaeus, 1758). Sixteen faecal samples out of 29 from Taim a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
(38 reference statements)
3
9
2
Order By: Relevance
“…Interestingly, seven alleles detected in the studied population were not observed in the blood/tissue set of samples from southern Brazil, also highlighting the great potential of these loci for local genetic studies. Levels of microsatellite polymorphism such as observed heterozygosity (H O = 0.832) and mean number of alleles (6.5) were higher in the present study than those reported for two other populations from southernmost Brazil (HO = 0.299/0.355; Weber et al, 2009) based on a partially overlapping set of loci, and also higher than that estimated for a wild population in Mexico (HO range = 0.48-0.59; Ortega et al, 2012).…”
Section: Success and Genetic Diversitycontrasting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, seven alleles detected in the studied population were not observed in the blood/tissue set of samples from southern Brazil, also highlighting the great potential of these loci for local genetic studies. Levels of microsatellite polymorphism such as observed heterozygosity (H O = 0.832) and mean number of alleles (6.5) were higher in the present study than those reported for two other populations from southernmost Brazil (HO = 0.299/0.355; Weber et al, 2009) based on a partially overlapping set of loci, and also higher than that estimated for a wild population in Mexico (HO range = 0.48-0.59; Ortega et al, 2012).…”
Section: Success and Genetic Diversitycontrasting
confidence: 87%
“…Gallo-Reynoso, Ramos-Rosas & Rangel-Aguilar, 2008;Chemes, Giraudo & Gil, 2010). Molecular studies are so far few, focusing mostly on the characterization of genetic diversity and/or population structure (Trinca, Waldemarin & Eizirik, 2007;Weber et al, 2009;Ortega, Navarrete & Maldonado, 2012;. There is thus a need to investigate its biology in more detail, including the use of molecular tools to address outstanding questions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our estimates of dispersion levels between rivers suggest that they are high enough to prevent genetic differentiation. The pattern of low genetic structure is also strongly supported by the high resolution provided by microsatellite markers in these types of studies (Selkoe & Toonen 2006;Weber et al, 2009). In particular, Latch et al (2008) found that the North American river otter (L. canadensis) in Louisiana is affected by a variety of landscape habitats that have structured the river otter populations and have prohibited an adequate level of gene flow, but the scale of that study is several times larger than the area surveyed in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Information concerning population dynamics of the species is scarce, and even less is known about the genetic structure of their populations. Only two studies related to the genetic structure of the neotropical river otter have been conducted previously in Brazil, but both were carried out in larger areas than our present study (Trinca et al, 2007;Weber et al, 2009). The first study found no significant mtDNA genetic differentiation between populations in the southern and south-eastern regions of Brazil and the latter study, using microsatellite markers, found significant levels of genetic differentiation in populations in the southernmost part of Brazil.…”
Section: Discussioncontrasting
confidence: 45%
“…In the first study of L. longicaudis using nuclear markers, Weber et al (2009) collected 43 stool samples in the state of Rio Grande do Sul and tested the amplification of five microsatellites developed for Lutra lutra. The genotyping efficiency reached 37 % and 24 genotypes were detected.…”
Section: Introductionmentioning
confidence: 99%